Radar-derived Surface Current Fields along RV MARIA S. MERIAN cruise track MSM89 - Ruben Carrasco; Michael Streßer; Jochen Horstmann; Johannes Karstensen (PANGAEA, 2023)
The dataset contains near surface current fields observed between January 23, 2020, and February 19, 2020 in. Currents were derived from radar data acquired with a Hereon X-band marine radar (Horstmann et al., 2021). The radar was deployed on the research vessel Maria S. Merian during the research cruise MSM89 for the EUREC4A-OA project. The provided data reflects the eastward (u) and northward (v) component of the near surface current vector. The effective depth of the retrieved currents depends on the waves present (longer waves feel the current at greater depth). Here, the current data corresponds approximatley to a depth between 2 m and 10 m.